Campur Kode Dan Alih Kode Dalam Teks Ginem/Dialog Pedalangan (Kajian Sosiolinguistik) - Sri Hesti Heriawati (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2007)
Sociolinguistics as a linguistics branch puts language in relation to the language usage. According to sociolinguistics point of view, language has variations. A sociolinguistics explains about the relation between variations and the social and situational aspect. In connection with the various usage of language, there appears what is called dwibahasawan (bilingualist). The effects the language used by the dalang which includes non puppet language anytime. The phenomenon of language usage changing because of the changing situation is called alih kode (code change). Alih kode is usually followed by campur kode (code mix) that is basic code which used and has autonomous function. A speaker who inserts other language into the language which he is using is called campur kode. Background of campur kode and alih kode can be seen in the language used by the user which uses more than one language. The special characteristics of the speaker will color his campur kode. A speaker who has mastered more than one language will has a change to execute campur kode. But it doesnâ€™t mean that a speaker who has mastered more than one language always have more campur kode.Â Key words: sociolinguistics, campur kode, alih kode.